PENGEMBANGAN MEDIA PEMBELAJARAN ATM BKC (BACA KERJAKAN COCOKKAN) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS IV SD MUHAMMADIYAH SENGGOTAN YOGYAKARTA - Tutut Farida; Danuri Danuri (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2021)
This research purpose to: (1) study the development of ATM BKC learning media, (2) assess the eligibility of ATM BKC for Elementary grade IV math as learning media as evaluated by material expert, media expert, teachers’ response, students’ response and (3) assess the progress in students’ academic achievement in elementary grade IV math lesson based on their scores. This research took place in Elementary School (SD) MuhammadiyahSenggotan during 2018/2019 academic year. Development procedures encompassed: analysis, design, development, implementation and evaluation also known as ADDIE. Data collection technique relied on observation leaf concerning completion of learning, questionnaire and test. Data analysis makes use of score percentage, tables, score interpretation and t-test using paired sample t-test. The result of the research can be described as follows: (1) the development of ATM BKC media using ADDIE procedure contains 5 stages i.e. analysis, design, development, implementation, evaluation; (2) ATM BKC media is eligible for learning practice. Score from material expert is 34 with very good qualification; score from media expert in 36 with very good qualification, teachers’ response questionnaire in preliminary field testing resulted in score 36 with very good qualification, students’ response during preliminary field testing resulted in percentage 97,5% with very good qualification, students’ response in main field testing is 79%^ with very good qualification. (3) ATM BKC media can improve students’ academic achievement as evidenced by the result of before group’s pretest score 45,5. As for after group their score is  50 in pretest and 78 in posttest. Therefore it can be concluded that the posttest score of pupils in SD Senggotan had improved. The scores of both before group and after group has sig. (2-tailed) score 0,000 <0,05. Therefore it can be concluded that ATM BKC under development already and is capable of improving students’ academic achievement in math lesson mixed numbers calculation.